Comparison of third generation ELISA and conventional nested RT-PCR for detection of HCV among hemodialysis patients - Shantanu Prakash, S.N. Sankhwar, Amita Jain, Kausar Usman, Narayan Prasad, D. Saha, K.P Singh, Parul Jain and Desh Deepak Singh (Journal of Applied Pharmaceutical Science, 2014)
Hepatitis C virus is one of the main cause of chronic hepatitis in developing countries. The current study was done to evaluate the efficacy of the third generation ELISA compared to nested RT- PCR for establishing the diagnosis of hepatitis C virus (HCV) in patients on hemodialysis. This descriptive, cross-sectional study was carried out on 237 Hemodialysis patients in Lucknow, Uttar Pradesh. The retrospective demographic data of the subjects was collected and the patient’s serum samples were analyzed by ELISA & RT-PCR for HCV. In the present study, of total 21 HCV positive either by ELISA or PCR 12 (57.14%) were positive for both RT-nested PCR and ELISA. Total four (19.05%) patients were positive for HCV by RT-nested PCR and negative by ELISA while five (23.81%) patients were negative for RT-nested PCR and positive for ELISA. PCR method is accredited as a specific and reliable method suitable for screening of HCV and is recommended for establishing exact and final diagnosis of these patients. However third generation ELISA assays have many advantages in the diagnostic setting including ease of automation, ease of use, relative cost-effectiveness, and low variability.
Keywords: ELISA, RT-PCR, Hepatitis C virus & hemodialysis.